Rationale, design, and preliminary results of the Quebec Warfarin Cohort Study. Issue 5 (15th May 2018) - Perreault, Sylvie; Shahabi, Payman; Côté, Robert; Dumas, Stéphanie; Rouleau‐Mailloux, Étienne; Feroz Zada, Yassamin; Provost, Sylvie; Mongrain, Ian; Dorais, Marc; Huynh, Thao; Kouz, Simon; Diaz, Ariel; et al.
Abstract : Over‐ and undercoagulation with warfarin are associated with hemorrhagic and thromboembolic events, respectively. Genetic and clinical factors affect warfarin response, and the causes of this variability remain unclear. We present descriptive statistics and test for predictors of poor anticoagulation control. The Quebec Warfarin Cohort (QWC) comprises 1059 new warfarin users, with prospective follow‐up using telephone questionnaires every 3 months for 1 year, and using healthcare administrative databases (RAMQ and Med‐Echo) for 5 years prior to cohort entry and up to 10 years following active patient participation. Genetic material was collected, and genotyping of CYP2C9 and VKORC1 genes was conducted. Measured outcomes included the percentage of time patients spent within therapeutic range, anticoagulation control, warfarin dose, bleeding, and thromboembolic events. We report baseline characteristics and outcomes after 1 year of follow‐up. Poor anticoagulation control was defined as time in therapeutic range <60% in the 3‐ to 12‐month interval. Participants had a mean age of 71 years, and 62% were men. The most common indication for warfarin was atrial fibrillation (87%). Mean time in therapeutic range was 56% (±25%) in the 3 months following warfarin initiation, and 70% (±21%) in the 3‐ to 12‐month interval. During follow‐up, the rate of stroke or systemic embolism was 1.8 events per 100 person‐years; for major bleeding events, 3.3 events per 100 person‐years. Independent predictors of poor anticoagulation control were chronic kidney disease, heart failure, dyslipidemia, and age. The QWC represents a good research cohort to investigate clinical and genetic factors in a warfarin‐anticoagulated population.